2017
DOI: 10.2147/ijwh.s108905
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of birth defects in a tertiary health facility in the Niger Delta area of Nigeria

Abstract: ObjectiveTo ascertain the prevalence and pattern of congenital abnormalities that are peculiar to the Niger Delta area of Nigeria.MethodsThis is a descriptive retrospective cross-sectional study. It involved data from the labor ward and neonatal birth registers of the University of Port Harcourt Teaching Hospital on the total number of births and the babies that were delivered with major birth defects between August 2011 and December 2014. We also conducted a statistical comparison of the prevalence of congeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 9 publications
5
26
1
Order By: Relevance
“…Chromosomal abnormality is a major contributor to birth defects, with autosomal trisomies 21, 18 and 13 (T21, T18, T13) and sex chromosome aneuploidy (SCA) being the most common. In China, the predominant approach for detection of fetal aneuploidy is first‐ and second‐trimester maternal serum screening in combination with ultrasound examination.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal abnormality is a major contributor to birth defects, with autosomal trisomies 21, 18 and 13 (T21, T18, T13) and sex chromosome aneuploidy (SCA) being the most common. In China, the predominant approach for detection of fetal aneuploidy is first‐ and second‐trimester maternal serum screening in combination with ultrasound examination.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Europe, a perinatal death of 2.0% in the form of stillbirths or fetal deaths and neonatal deaths (2.5%) in the first week of life are attributed to congenital anomaly . In Nigeria, available data on congenital malformations are mostly from hospital‐based studies . Abbey et al .…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, available data on congenital malformations are mostly from hospital‐based studies . Abbey et al . in a descriptive retrospective cross‐sectional study conducted in a Nigerian teaching hospital reported a prevalence of 20.73 cases per 1000 live births, with the frequency in unbooked maternities significantly higher than the booked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] There are also reported adverse effects of this exposure on fetal development and outcomes of pregnancy from paternal and maternal associated factors. 5,6 Since Yenagoa is a city in an oil producing area, there is a need to report for the first time HPE in order to encourage more researches and highlight challenging issues associated with its management in the area. The WHO estimated that neonatal deaths from congenital anomalies worldwide increased from 260,000 (7% of all neonatal deaths) in 2004 to 303 000 (11.6% of all neonatal deaths) in 2016.…”
Section: Introductionmentioning
confidence: 99%